2014
DOI: 10.1109/tmc.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Outage in Mobile Random Networks: Expectation, Distribution, and Correlation

Abstract: In mobile networks, distance variations caused by node mobility generate fluctuations in the channel gains. Such fluctuations can be treated as another type of fading besides multi-path effects. In this paper, the interference statistics in mobile random networks are characterized by mapping the distance variations of mobile nodes to the channel gain fluctuations. The network performance is evaluated in terms of the outage probability. Compared to a static network, the interference distribution in a single sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 48 publications
3
163
0
1
Order By: Relevance
“…S. Weber analyzes the phenomenon of interference in ad-hoc networks in terms of transmission capacity which derives from the outage probability. In [11], Z. Gong gives, based on the estimation of outage probability in mobile random networks, results that show the importance of routing, MAC and retransmissions schemes to avoid bursts of transmission failures.…”
Section: Related Workmentioning
confidence: 99%
“…S. Weber analyzes the phenomenon of interference in ad-hoc networks in terms of transmission capacity which derives from the outage probability. In [11], Z. Gong gives, based on the estimation of outage probability in mobile random networks, results that show the importance of routing, MAC and retransmissions schemes to avoid bursts of transmission failures.…”
Section: Related Workmentioning
confidence: 99%
“…Each BSN moves according to the random waypoint model [26]- [28]. As pointed out by Gong and Haenggi [19], the random 1 The configuration settings of Changi General Hospital and Tan Tock Seng Hospital in Singapore Path-loss exponent of inter-body channel model I a 3…”
Section: A Simulation Settingsmentioning
confidence: 99%
“…Compared to the existing stochastic geometry analysis [9], [17]- [19], we relax the assumptions that each node in the network follows the same MAC operation mode at a given time. In our study, although all the BSNs employ the hybrid MAC structure defined in IEEE 802.15.6, a specific BSN may operate at either contention-based or contention-free state at a given time in the absence of global synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…According to different configurations for the receiver, the lines of recent literature can be divided into three categories: the correlations between different time slots [9], [10], [11], [12], the correlations between different receive antennas [13], and the correlations between different receivers [14]. The interference correlation was first investigated in ALOHA ad hoc network whose nodes are distributed as a PPP [10].…”
Section: Csit] 25 Nov 2014mentioning
confidence: 99%
“…In that work, the closed-form expression of the joint success probability is a special case of the main result in [11]. In [12], the temporal interference correlation in mobile Poisson networks was quantified in terms of the correlation coefficient and conditional outage probability. The results showed that smart routing, retransmission, and multiple access control schemes are needed to avoid bursts of transmission failures.…”
Section: Csit] 25 Nov 2014mentioning
confidence: 99%